Diplomasi Koersif Amerika Serikat Terhadap Indonesia Melalui Embargo 1991-2005 - Ira Rizka Aisyah Lubis (Universitas Medan Area, 2022)
This article aims to analyze the effectiveness of the coercive diplomacy carried out by the United States against Indonesia. These coercive diplomatic actions are in the form of embargoes, such as arms embargoes and IMET Ban. This study uses qualitative research methods using secondary data. The long duration of the IMET Ban and the arms embargo that occurred more than once made the United States' coercive diplomacy towards Indonesia look ineffective. Therefore, this study raises the research question